2013
DOI: 10.1093/nar/gkt251
|View full text |Cite
|
Sign up to set email alerts
|

Loop-miRs: active microRNAs generated from single-stranded loop regions

Abstract: MicroRNAs (miRNAs) are key mediators of post-transcriptional gene regulation. The miRNA precursors are processed by the endonucleases Drosha and Dicer into a duplex, bound to an Argonaute protein and unwound into two single-stranded miRNAs. Although alternative ways to generate miRNAs have been discovered, e.g. pre-miRNA cleavage by Ago2 or cleavage products of snoRNAs or tRNAs, all known pathways converge on a double-stranded RNA duplex. Exogenous single-stranded siRNAs (ss-siRNAs) can elicit an effective RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 68 publications
(43 reference statements)
2
50
0
1
Order By: Relevance
“…Because isomiRs contain different sequences, they may have different targets and thus different cell functions [19]. Great sequencing depth and careful data mining also reveal moRs (microRNA-offset RNAs) [2022] and single strand RNA fragments released from the loop RNA portion of the precursor miRNA hairpin [23,24] (which we call “loop-origin miRNAs”, or “loRs”). Although functional evidence remains scarce, these variants appear to be independently regulated and may play cooperative, complementary, or alternative roles in cell function and gene regulation compared to their associated miRNAs.…”
Section: Small Rnas and Their Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because isomiRs contain different sequences, they may have different targets and thus different cell functions [19]. Great sequencing depth and careful data mining also reveal moRs (microRNA-offset RNAs) [2022] and single strand RNA fragments released from the loop RNA portion of the precursor miRNA hairpin [23,24] (which we call “loop-origin miRNAs”, or “loRs”). Although functional evidence remains scarce, these variants appear to be independently regulated and may play cooperative, complementary, or alternative roles in cell function and gene regulation compared to their associated miRNAs.…”
Section: Small Rnas and Their Functionsmentioning
confidence: 99%
“…Small RNA sequencing libraries also identify sequences that derive from the loop of pre-MiRNAs and, like moRs, their relative quantities can vary according to tissue or developmental stage [23,24], suggesting independent regulation of expression and thus independent cell functions. Furthermore, recent studies reported the expression and incorporation of loop-derived short sequences into the RISC and repression of translation of targeted mRNA in in vitro luciferase assays [23,24].…”
Section: Other Relevant Microrna Productsmentioning
confidence: 99%
“…While this article was in production, another study (Winter et al 2013) came to our attention describing functional miRNA loop species in human cells.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…However, highly conserved passenger strands 5 , 6 can also be incorporated into RISCs and serve as active miRNAs bound to Argonaute (Ago) proteins. Additionally, the loop region can give rise to a loop-miR 7 , 8 . For some miRNAs, both arms of the pre-miRNA hairpin are found in RISCs in significant amounts underlining the functional relevance of these less abundant products of miRNA biogenesis 9 .…”
Section: Introductionmentioning
confidence: 99%